PENYULUHAN DAN PEMERIKSAAN KADAR HEMOGLOBIN SEBAGAI SALAH SATU UPAYA DETEKSI DINI ANEMIA PADA IBU HAMIL: Counseling - Hardaniyati Hardaniyati; Irni Setyawati; Dian Soekmawaty Riezqy Ariendha; Yesvi Zulfiana (Stikes Yarsi Mataram, 2022)
The high prevalence of anemia has negative consequences such as the firstdisturbance and inhibition of growth, both body cells and brain cells, while thesecond deficiency of Hb in the blood results in a lack of oxygen beingcarried/transferred to body cells and to the brain. The incidence of anemia inpregnant women in Indonesia is still high, namely 37.1, the prevalence ofanemia in pregnant women in Indonesia is 37.1%. cases of anemia in pregnant women have increased every year, namely in 2015 at the Sengkol HealthCenter as many as 200 cases, and in 2016 as many as 251 cases. Hemoglobinlevels as an early detection of anemia in pregnant women.His communityservice partner is the Chair of STIKes Yarsi Mataram and the Head of theMidwifery Study Program for the Bachelor program. This service to thecommunity uses the method of counseling and checking the hemoglobin ofpregnantwomen using the